Pengaruh Reward dan Punishment terhadap Kinerja Karyawan Bank Syariah di Sumatera Barat - Gampito; Candra, Revi; Elfadhli (Al-bank: Journal of Islamic Banking and Finance, 2025)
This study aims to analyze the effect of reward and punishment on the performance of Islamic bank employees in West Sumatra. Reward is measured through job promotion and bonus, while punishment is measured through demotion and mutation. This research employed a quantitative approach using a survey method with questionnaires distributed to employees of Islamic banks in West Sumatra. The data were analyzed using multiple linear regression. The findings reveal that job promotion, bonus, and demotion have a positive and significant effect on employee performance, while mutation does not have a significant effect. Simultaneously, reward and punishment significantly influence employee performance. These results highlight the importance of implementing a transparent and fair reward and punishment system to improve employee performance in Islamic banking institutions. The implication of this study suggests that Islamic banks should strengthen policies related to promotion and bonus distribution, while carefully reviewing the effectiveness of employee mutation to avoid potential negative impacts on performance. In addition, the findings provide academic insight into human resource management practices within Islamic banking and can serve as a reference for future research